Wireless Computer Network (WLAN) Security Test at Pradita University - Banu Bagaskara; Handri Santoso (TEPIAN, 2023)
In this day and age, information technology has developed rapidly, one of which is wireless computer network technology called Wireless Local Area Network (WLAN). Agencies and individuals have widely used the use of wireless computer networks. Because with a wireless computer network, it is easy to connect the devices so that your work becomes quickly completed. Along with the development of wireless computer networks, problems will undoubtedly arise, one of which is about network security in wireless technology; therefore, to maintain network stability, it is necessary to conduct periodic evaluations. To analyze network security with the Penetration Testing method simulated attacks on the network, the operating system with the correct specifications is Kali Linux. Kali Linux is designed for network security testing, equipped with tools that support hacking activities, and as a tool to test network security. The results of this research can later be used to improve the security of wireless computer networks at Pradita University. This study concludes that during the design of WLAN Network Security Analysis using attacks (Cracking The Encryption, Denial of Service, and MITM) using Kali Linux at Pradita University, it can be concluded that the security owned by the Pradita University WLAN network still has many loopholes to exploit.